First report of some known Trichodinella epizootica Šramek-Hušek, 1953, and Tripartiella Lom, 1959 from the cultured Oranda Gold Fish (Carassius auratus auratus) in India - Saha, Mandira; Bandyopadhyay, P.k. (Zootaxa, 2016)
Trichodiniasis of fishes cause economic losses in the fish industry through mortality and decrease growth rate. Very few studies of these ectoparasites have been made in India. A comprehensive icthyoparasotological survey in some ornamental fish farms of different parts of India has been done since March 2014–May 2015. During the study these trichodinid parasites have been identified from the gills of Oranda Gold Fish (Carassius auratus auratus L.). They are Trichodinella epizootica, Tripartiella viz. Tripartiella bulbosa, Tripartiella copiosa and Tripartiella obtusa. All these parasites have been recorded for the first time from the gills of Oranda Gold Fish (Carassius auratus auratus L.) in India i.e. The paper deals with the diversity and description of ciliophorans parasites of ornamental fish.